The Experience in Designing and Building the High Performance Cluster Netuno - Silva, Gabriel P.; Correa, Juliana; Bentes, Cristiana; Guedes, Sergio; Gabioux, Mariela (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2011: Anais do XXIII International Symposium on Computer Architecture and High Performance Computing, 2011)
This paper presents a description and the evaluation of the Netuno supercomputer, a high-performance cluster installed at Federal University of Rio de Janeiro in Brazil. The results for the High Performance Linpack (HPL) benchmark and two real applications are reported. Since building a high-performance cluster for running a wide range of applications is a non-trivial task, some lessons learned from assembling and operating this cluster, such as the excelent performance of the OpenMPI library, and the importance of the use an efficient parallel file system over the traditional NFS system, can be useful knowledge to support the design of new systems. Currently, Netuno is being heavily used to run large scale simulations in the areas of ocean modeling, meteorology, engineering, physics, and geophysics.